The party crasher [compact disc, unabridged] : a novel - Kinsella, Sophie (Random House Audio, 2021)
It's been over two years since Effie's beloved parents got divorced, destroying the image of the happy, loving childhood she thought she had. Since then, she's become estranged from her father and embarked on a feud with his hot (and much younger) girlfriend, Krista. And now, more earth-shattering news: Greenoaks, the rambling Victorian country house Effie called home her whole life, has been sold. When Krista decides to throw a grand "house cooling" party, Effie is originally left off the guest list--and then receives a last-minute "anti-invitation." Effie declines, but then remembers a beloved childhood treasure is still hidden in the house. Her only chance to retrieve it is to break into Greenoaks while everyone is busy celebrating. As Effie sneaks around the house, hiding under tables and peeping through trapdoors, she realizes the secrets Greenoaks holds aren't just in the dusty passageways and hidden attics she grew up exploring.